Hemorrhagic complications of pancreatitis in surgical practice - L. A. Neledova; D. V. Mizgiriov; B. L. Duberman (Вестник хирургии имени И.И. Грекова, 2019)
The objective of the study was to detect the frequency and sources of hemorrhagic complications in patients with pancreatitis, evaluate the tactics and effectiveness of methods of hemostasis. Material and methods. A retrospective analysis of hemorrhagic complications of pancreatitis was carried out in 40 patients. Results. Bleeding developed mainly on the background of infected acute necrotic collections (77.8 %), the main source of bleeding was the splenic artery (37.0 %). Emergency laparotomy for bleeding was performed in 9 (22.5 %) patients, selective angiography was performed in 10 patients, it was effective only in 5 (50 %) cases. 12 (44.4 %) deaths were recorded in cases of arrosive bleeding. Conclusion. The preferred tactics in case of bleeding from the retroperitoneal space during minimally invasive treatment is crossclamping of drains and endovascular hemostasis.